Causes of the Emergence of Deviant Behavioral Types and Methodology for Their Diagnosis - Dilnoza Eshnazar qizi Ahmedova (Scientific Trends, 2025)
This article discusses the growing social importance of psychology as a science that studies the interrelationship between society and nature. Special attention is given to the psychology of children with behavioral deviations, the relevance of the topic, types of deviant behavior, the factors causing such behavior, and methods for psychological diagnosis. The article also considers multidisciplinary approaches (psychological, pedagogical, legal, and sociological) to the problem of deviant behavior.
Keywords: Psychology, deviant children, deviant behavior, prevention, social-psychological support, personality, social norms, radical adaptation, hyperadaptation, conformistic adaptation, conformist adaptation, deviant adaptation, social-psychological maladjustment, dependent behavior, suicide, aggression.